2014
DOI: 10.5230/jgc.2014.14.3.196
|View full text |Cite
|
Sign up to set email alerts
|

Expression Levels of Vascular Endothelial Growth Factors A and C in Patients with Peptic Ulcers and Gastric Cancer

Abstract: PurposeVascular endothelial growth factor (VEGF) is one of the most important growth factors for metastatic tumors. To clarify the role of VEGF-A and C in patients with peptic ulcer disease (PUD) or gastric cancer (GC), we evaluated the expression levels of these two molecules. We also analyzed the effect of Helicobacter pylori infection on VEGF-A and C expression levels.Materials and MethodsPatients with dyspepsia who needed diagnostic endoscopy were selected and divided into three groups: non-ulcer dyspepsia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In addition, several determinants in GC development such as vascular endothelial growth factor-A and -C (VEGFA and VEGFC) were shown to be overexpressed in H . pylori -positive GC patients and their clinical significances were investigated ( 11 ). However, despite all these efforts to identify only a limited number of GC tissue-based biomarkers with prognostic values for H .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several determinants in GC development such as vascular endothelial growth factor-A and -C (VEGFA and VEGFC) were shown to be overexpressed in H . pylori -positive GC patients and their clinical significances were investigated ( 11 ). However, despite all these efforts to identify only a limited number of GC tissue-based biomarkers with prognostic values for H .…”
Section: Introductionmentioning
confidence: 99%
“…Gram staining. Oxidase and catalase tests 13 GC: 2 tissues at an early stage and 11 tissues at an advanced stage; 6 intestinal type tissues, 4 diffuse type tissues, and 3 mixed type tissues Pathological diagnosis 32.5 (18.57 to 49.13) Yu et al [ 132 ] China 1992 -2007 2014 CS 217 59.15 IHC -PCR 116 intestinal type:97, diffuse type: 95 Histopathology 53.46 (46.58 to 60.24) Zabaglia et al [ 45 ] Brazil - 2017 PCS 72 65,6 PCR 19 GC Histopathology 26.39 (16.7 to 38.1) Szkaradkiewicz et al [ 46 ] Poland 2013–2014 2016 CS 42 65 PCR 15 GC Histopathology 35.71 (21.55 to 51.97) Jorge et al [ 47 ] Brazil - 2013 PCS 27 63.4 Multiplex PCR 11 Intestinal: 12 Diffuse type: 8 Histopathology 40.74 (22.39 to 61.2) Taghizadeh et al [ 48 ] Iran 2012 -2013 ...…”
Section: Resultsmentioning
confidence: 99%
“…pylori -induced ulcers 26 . Meanwhile, recent evidence has suggested that elevated expression levels of endothelial growth factor C in gastric mucosal inflammation induced by sleep apnea, sleep loss, and nighttime hypoxia are likely to increase the risk of developing PUD 27,28 .…”
Section: Discussionmentioning
confidence: 99%